2020
DOI: 10.1128/jb.00751-19
|View full text |Cite
|
Sign up to set email alerts
|

Mild Stress Conditions during Laboratory Culture Promote the Proliferation of Mutations That Negatively Affect Sigma B Activity in Listeria monocytogenes

Abstract: In Listeria monocytogenes, the full details of how stress signals are integrated into the σB regulatory pathway are not yet available. To help shed light on this question, we investigated a collection of transposon mutants that were predicted to have compromised activity of the alternative sigma factor B (σB). These mutants were tested for acid tolerance, a trait that is known to be under σB regulation, and they were found to display increased acid sensitivity, similar to a mutant lacking σB (ΔsigB). The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 79 publications
3
54
0
Order By: Relevance
“…Both regulators are modulated by complex multi-layered control circuitry, highlighting the importance to fitness of deploying these systems only when the prevailing conditions are suitable. We have seen clear evidence that there is a significant burden on resources associated with deploying the GSR (Guerreiro et al, 2020) and a similar cost has been reported for inappropriate activation of PrfA (Bruno and Freitag, 2010). Clarification of the nature of the regulatory crosstalk between these systems will give new insights into the biology of this human pathogen as well as suggesting new approaches to control it.…”
Section: Future Perspectives and Challengesmentioning
confidence: 56%
See 1 more Smart Citation
“…Both regulators are modulated by complex multi-layered control circuitry, highlighting the importance to fitness of deploying these systems only when the prevailing conditions are suitable. We have seen clear evidence that there is a significant burden on resources associated with deploying the GSR (Guerreiro et al, 2020) and a similar cost has been reported for inappropriate activation of PrfA (Bruno and Freitag, 2010). Clarification of the nature of the regulatory crosstalk between these systems will give new insights into the biology of this human pathogen as well as suggesting new approaches to control it.…”
Section: Future Perspectives and Challengesmentioning
confidence: 56%
“…Following the release of RsbT and consequent activation of σ B , a negative feedback mechanism controlled by the phosphatase RsbX allows the stressosome to be reset to its non-stressed dephosphorylated state, which leads to the recapture of RsbT ( Voelker et al, 1997 ; Chen et al, 2004 ; Eymann et al, 2011 ). Deletion of rsbX produces a constitutive σ B activation and consequently increased survival in acidic conditions ( Xia et al, 2016 ) and a reduced competitiveness against a WT strain, a consequence of the reduced growth rate associated with increased σ B activity ( Guerreiro et al, 2020 ) (see section “σ B Deployment Is a Double-Edged Sword”).…”
Section: Insights Into the Mechanism Of Stress Sensing By The Stressomentioning
confidence: 99%
“…Metagenomic studies can give information on many levels starting from species composition down to specific pathways and genes (Quatrini and Johnson, 2018). Linking genomics tools with phenotypical studies will definitely bring more insight into genetic mechanisms behind microbial responses to acidic environment (Guerreiro et al, 2020). Mathematical modeling and computational approaches will also play an important role in understanding microbial physiological processes during acid adaptation (Mancini et al, 2020) and interactions between bacteria (Ratzke and Gore, 2017).…”
Section: Experimental Approaches To Study Low Ph Responsesmentioning
confidence: 99%
“…In C. difficile , the phosphatase RsbZ is responsible for RsbV dephosphorylation ( 11 ). The tight regulation of σ B activity by a partner-switching mechanism is necessary, as the energy burden associated with σ B activity was found to be disadvantageous in several different organisms ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%